"Time for recovery" or "utter uncertainty"? The postponement of the Tokyo 2020 Olympic Games through the eyes of Olympic athletes and coaches. A qualitative study - Oblinger-Peters, V.; Krenn, B. (Frontiers in Psychology, 2020)
The current COVID-19 pandemic has affected the entire globe, including the world of high-performance sports. Accordingly, it has been widely assumed that the thereby caused postponement of the Tokyo 2020 Olympic Games could have negative psychological impacts for aspirants, since they were halted abruptly in the pursuit of their Olympic endeavors and their daily lives drastically altered. Considering the sudden nature of the pandemic, few researchers, if any, have yet scrutinized the individual experience of Olympic aspirants. This qualitative study examines the subjective perceptions of the Tokyo 2020 Olympic Games postponement among Austrian Olympic athletes and coaches. To this end, 21 Austrian athletes (13 male, 8 female; mean age = 26.67 ± 4.93 years) and six male coaches were recruited through a criterion-based purposive sampling strategy. Five athletes had already qualified for the Olympic Games in Tokyo 2020 and 15 athletes were still in an ongoing qualification process. Data was collected by means of short written statements, elicited via open-format questions on an anonymous online survey platform. In order to infer meaning from the text, a qualitative content analysis with an interpretative focus was conducted inductively, which allowed for deriving alternative explanations of findings. The results support the notion that the Olympic postponement was experienced in myriad ways by affected participants. Three general themes comprised of several meaning units of different levels of abstraction were created from the text data. Many respondents experienced an immediate emotional reaction to the postponement characterized by confusion, disappointment and/or relief. Participants associated multiple consequences with the postponement, such as the prolongation of physical and psychological pressure, a lack of motivation, concerns about future performance, living and their occupational career, but also the opportunity for performance improvement and recovery. Respondents displayed various coping strategies, such as distancing themselves from sports, cognitive reframing, appealing for acceptance, and planning behavior. This study gleans first insights into the idiosyncratic experience of the Olympic Games 2020 postponement among Austrian aspirants. The findings could serve to assist sport psychologists in their applied practice by informing them about athletes` and coaches` needs in their Olympic preparation during the ongoing pandemic.